2018
DOI: 10.1080/14756366.2018.1455676
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule KDM4s inhibitors as anti-cancer agents

Abstract: Histone demethylation is a vital process in epigenetic regulation of gene expression. A number of histone demethylases are present to control the methylated states of histone. Among these enzymes, KDM4s are one subfamily of JmjC KDMs and play important roles in both normal and cancer cells. The discovery of KDM4s inhibitors is a potential therapeutic strategy against different diseases including cancer. Here, we summarize the development of KDM4s inhibitors and some related pharmaceutical information to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 132 publications
(163 reference statements)
0
25
0
Order By: Relevance
“…Three representative human 2OG oxygenases, for which structures in complex with 2,4-PDCA have been reported, were employed in the inhibition studies: AspH [14] , FIH [24] , and KDM4E [25] . KDM4E was used as a representative JmjC KDM; it catalyzes the demethylation of histone 3 (H3) N ε -di- and trimethylated Lys9 (H3K9me3/me2) [10] , [11] , [12] . The inhibitory effect of 2,4-PDCA and its derivatives was also investigated for human RIOX2, though a structure of RIOX2 in complex with 2,4-PDCA has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three representative human 2OG oxygenases, for which structures in complex with 2,4-PDCA have been reported, were employed in the inhibition studies: AspH [14] , FIH [24] , and KDM4E [25] . KDM4E was used as a representative JmjC KDM; it catalyzes the demethylation of histone 3 (H3) N ε -di- and trimethylated Lys9 (H3K9me3/me2) [10] , [11] , [12] . The inhibitory effect of 2,4-PDCA and its derivatives was also investigated for human RIOX2, though a structure of RIOX2 in complex with 2,4-PDCA has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…The development of potent and selective inhibitors for 2OG hydroxylases other than the PHDs is of basic scientific (for use in functional assignment studies) and therapeutic interest, in the latter case for diseases including cancer [4] . For example, aspartate/asparagine-β-hydroxylase (AspH), which catalyzes the stereoselective C3 hydroxylation of Asp/Asn-residues that are part of specific disulfide isomers of epidermal growth factor-like domains (EGFDs) [5] , [6] , [7] , and certain JmjC lysine-specific N ε -demethylases, which catalyze the N ε -lysine demethylation of histones via initial N ε -methyl-group hydroxylation followed by fragmentation to give formaldehyde as a coproduct (Supporting Figure S1), are current medicinal chemistry targets for cancer treatment [8] , [9] , [10] , [11] , [12] .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Also, the replacement of the 4‐carboxylate group with a pyrido[3,4‐d]pyrimidin‐4(3H)‐one group enhances cellular permeability . Additionally, some 3‐amino‐4‐pyridine carboxylate derivatives have been identified as KDM4 inhibitors …”
Section: Kdm4 Inhibitors As Novel Epigenetic Cancer Agentsmentioning
confidence: 99%
“…209 Additionally, some 3-amino-4-pyridine carboxylate derivatives have been identified as KDM4 inhibitors. 193 More recent work with cyclic peptides targeting KDM4 has revealed that high selectivity can be accomplished via substrate competitive inhibitors. Crystal structural and biochemical analyses of KDM4A with its inhibitor indicate that macrocyclic peptide CP2 competes with the histone in the substrate-binding pocket despite different binding mechanisms.…”
Section: Histone Substrate Competitive Inhibitorsmentioning
confidence: 99%
“…Several small molecules have been developed that inhibit KDM4A demethylase activity while typically also inhibiting multiple related demethylases (reviewed in-depth [ 60 ]). Briefly, 8-Hydroxyquinoline derivatives and pyridine-based inhibitors showed promise as clinically relevant KDM inhibitors but failed to discriminate between KDMs [ 60 , 61 ]. Currently, QC6352 a cell-permeable KDM4 family-specific inhibitor exhibited antiproliferative effects but was unable to discriminate within the KDM4s [ 62 ].…”
Section: Introductionmentioning
confidence: 99%